FINANCIAL LITERACY FOR ELEMENTARY SCHOOL STUDENTS IN MUARA PENIMBUNG ULU VILLAGE - Rahmawati, Meita; Patmawati, Patmawati; Daud, Rochmawati; Meutia, Inten; Sitepu, Christian Damar Sagara; Maryati, Sri (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Financial literacy is one of the six basic literacies agreed upon at the World Economic Forum, financial literacy must be taught and possessed by children, not only elementary school students (equivalent) in urban areas but also very much needed by elementary school students (equivalent) in rural areas, namely Muara Penimbung Ulu Village, Ogan Ilir Regency, with knowledge of financial literacy from an early age, it is hoped that it can help students in practicing managing their finances appropriately and usefully. If children already have and are able to apply financial literacy well from an early age, various aspects of their lives will be better in the future. Five basic principles are learned in financial literacy, namely business or work, shopping or consumption, saving, sharing, and borrowing. These materials and activities consist of: Types of financial literacy extracurricular activities, implementation of good practices of financial literacy extracurricular activities, and evaluation of the process of implementing financial literacy extracurricular activities. The target audience for this community service activity is elementary school teachers and students (equivalent) in Muara Penimbung Ulu Village, Indralaya District, Ogan Ilir Regency. The community service implementation method uses lectures, illustrations, and discussions.